Alignment of Outsourcing Agreement on Protection Law and Justice - Niru Anita Sinaga; Basuki Rekso Wibowo; Sri Gambir Melati Hatta; Fauzie Yusuf Hasibuan (The Southeast Asia Law Journal, 2015)
One of these systems outsourcing, in practice often raises the pros and cons even cause problems. The problem is why research in the outsourcing agreement must have harmony with the principles of contract law? and how legal protection for workers/laborers and employers in the outsourcing agreement with the labor Law No. 13 Year 2003 on Employment associated with Court Decision No. 27/PUU-IX/2011?. This research methods using empirical juridical normative juridical supported/sociological and comparative law. Commonly used secondary data. Based on the results of analysis show that the employment agreement outsourcing based on the principle of freedom of contract and the principle of the deal. Each of these parties do not have equal bargaining power, so it does not provide legal protection for workers/laborers. Preparation and implementation of the outsourcing agreement is based on the alignment of the entire principle or principles that exist in the law of contract, is a unity, without prioritizing or separating principle that one with the other principles and serve as the frame of the treaty.